Analisis Kesulitan Membaca Pada Siswa SD di Kabupaten Sumedang (Sebuah Studi Kasus) - Al Zahra, Syifa Shofia; Sunarya, Dede Tatang; Julia, J. (Jurnal Pena Ilmiah, 2021)
Reading difficulties are type of disability that students experience when learning to read; In the form of behaviors and habits can be carefully observed because they have distinct characteristics. There are many factors that affect reading difficulty. In general, they can be caused by internal and external factors. The researcher wanted to investigate the characteristics of reading difficulties that students had, the factors that influenced them, and the mentoring efforts they made. This study uses a qualitative approach using a case study design. Research data collected from interviews, observations, document analysis and field notes. The subjects of the study are fourth grade students with reading difficulties, parents and teachers of student who have reading difficulties. The results characterize reading comprehension difficulties faced by students are, (1) difficulty identifying specific letters, (2) adding, deleting and replacing words, (3) difficulty identifying difficult words and (4) not good in reading. The factors that cause reading difficulties in students are related to psychological conditions, parenting patterns and management of education. Accompaniment that given are an emotional approach and habituation.